Epstein-Barr Virus-Encoded Protein Kinase (BGLF4) Is Involved in Production of Infectious Virus - Gershburg, Edward (American Society for Microbiology, 2007)
The Epstein-Barr virus (EBV) BGLF4 gene product is a protein kinase (PK). Although this kinase has been characterized and several of its targets have been identified, its biological role remains enigmatic. We have generated and assessed a BGLF4 knockdown phenotype by means of RNA interference and report the following: (i) BGLF4-targeting small interfering RNA effectively inhibited the expression of its product, the viral PK, during lytic reactivation, (ii) BGLF4 knockdown partially inhibited viral DNA replication and expression of selected late viral genes, (iii) the absence of EBV PK resulted in retention of the viral nucleocapsids in the nuclei, and (iv) as a result of the nuclear retention, release of infectious virions is significantly retarded. Our results provide evidence that EBV PK plays an important role in nuclear egress of the virus and ultimately is crucial for lytic virus replication.